Deiktinės sistemos baltų kalbų tarmėse - Rosinas, Albertas (Baltistica, 1982)
Deictic systems in Baltic dialectsThe article is an attempt to investigate the Baltic deictic systems and to present the motivation of their systematic restructuring. The following conclusions can be drawn:1. Binomial deictic systems appear to predominate in Baltic dialects.2. The binomial deictic systems (as well as the one-member system in the Samogitian dialect) derive from three-member systems.3. The reconstruction of the common Baltic three-member deictic protosystem could be considered valid if it were to be assumed that the pronoun *vin(E) (j)is → viņš “that” had been early substituted for the Proto-Latvian pronoun *anas (cf. o-trs “second”
Keywords: deiktinės sistemos; baltų kalbų tarmės